Innovative ballast replacement material (IBRM) in-line with geo-technology pillar of IR4.0 in construction - Kirushna Moorthi, Jeevithan; Duraisamy, Youventharan; Rokiah, Othman; Mohd Arif, Sulaiman (2021)
To reduce the damages exerted on existing granite ballast, waste materials such as concrete debris from construction and demolition process and bottom ash from coal energy production mixed in different proportion with granite ballast, creating IBRM. IBRM will be scrutinized to replace the track ballast upto to 50% depending on the speed of train and load exerted on the rail.